An improved mapping of ice layer undulations for the IceCube Neutrino Observatory ... - IceCube; Abbasi, Rasha; Ackermann, Markus; Adams, Jenni; Agarwalla, Sanjib; Aguilar, Juanan; Ahlers, Markus; Alameddine, Jean-Marco; Amin, Najia Moureen Binte; Andeen, Karen; Anton, Gisela; Arguelles, Carlos; et al. (Scuola Internazionale Superiore di Studi Avanzati (SISSA), 2023)
A precise understanding of the optical properties of the instrumented Antarctic ice sheet is crucial to the performance of the IceCube Neutrino Observatory, a cubic-kilometer Cherenkov array of 5,160 digital optical modules (DOMs) deployed in the deep ice below the geographic South Pole. We present an update to the description of the ice tilt, which describes the undulation of layers of constant optical properties as a function of depth and transverse position in the detector. To date, tilt modeling has been based solely on stratigraphy measurements performed by a laser dust logger during the deployment of the array. We now show that it can independently be deduced using calibration data from LEDs located in the DOMs. The new fully volumetric tilt model not only confirms the magnitude of the tilt along the direction orthogonal to the ice flow obtained from prior dust logging, but also includes a newly discovered tilt component along the flow. ...